Dietary habits by income level during the COVID-19 pandemic in Indonesia: results from the IndoNutriLifeCOVID-19 online survey - Sorra Milwayani Septiyana; Arif Sabta Aji; Reznar, Melissa; Estradé, Michelle; Guo, Isabella; Yit, Siew Chin; Yoke, Mun Chan; Esti Nurwanti; Herwinda Kusuma Rahayu; Yulinda Kurniasari (Scientific Foundation SPIROSKI, Skopje, Republic of Macedonia, 2022)
Background: The Coronavirus Disease 2019 (COVID-19) has caused many lifestyle changes, especially in the diet. Policies such as physical distancing and quarantine orders aimed to mitigate to spread of COVID-19 have affected the economy and, therefore, the dietary habits of the people.